The impact of the Movement Control Order (MCO) on type of commercial activities in Muar town, Johor - Mohd Sapian, Muhammad Syafiq; Hassan, Mohd Azren; Abdullah, Yusfida Ayu; S. Muthuveeran, Adam Aruldewan; Yin, Izuandi; Nasrudin, Na’asah (Malaysian Institute Of Planners, 2023)
The COVID-19 pandemic has changed human nature. The Malaysian government declared the Movement Control Order as a measure to control the spread of COVID- 19 with various restrictions. The Movement Control Order has affected daily routines as well as commercial activities. Therefore, the study will focus on the impact of movement control orders during the COVID-19 pandemic on the operations, supply of materials and products, as well as finances of commercial activities at a district level. The town of Muar, Johor, has been identified as the commercial area for this study. The data collection was accomplished by a questionnaire survey and by using convenience sampling with 100 respondents answering the questionnaire. A crosstable analysis and a Pearson’s chi-squared test analysis were used to examine the Movement Control Order‘s implications on commercial activities’ operations, supply of materials and products, and finances. The findings indicated that the Movement Control Order had a substantial impact on commercial activities. The study concluded that cash flow for survival needs critical attention due to this unprecedented outbreak, which led to the economic downturn. It is recommended that the government offer training courses on digital marketing and e-commerce to boost commercial activities as part of a new business strategy and financial management plan, particularly for new businesses at the district level.